a + b + c + d b + c + d + e c + d + e + a d + e + a + b e + a + b + c = = = = = 1 2 3 4 6
What is the value of a e + b d + c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Adding all 5 sums gives 4 ∗ ( a + b + c + d + e ) = 1 6 ⇒ a + b + c + d + e = 4 ( 1 ) From this we can subtract the sums from ( 1 ) (for example we would say ( a + b + c + d + e ) − ( a + b + c + d ) = 4 − 1 ⇒ e = 3 ) to obtain the follwing results a = 2 , b = 1 , c = 0 , d = − 2 , e = 3 Therefore a e + b d + c = 2 3 + 1 − 2 + 0 = 8 + 1 = 9
If we sum all the equations then we get 4 ( a + b + c + d + e ) = 1 6 . Therefore a + b + c + d + e = 4 . Subbing in the initial equations gives us 5 new equations: a + 2 = 4 b + 3 = 4 c + 4 = 4 d + 6 = 4 e + 1 = 4 Solving these gives us the solution ( 2 , 1 , 0 , − 2 , 3 ) so a e + b d + c = 2 3 + 1 − 2 + 0 = 8 + 1 = 9
Problem Loading...
Note Loading...
Set Loading...
To find e:
Add all equations up to get 4a+4b+4c+4d+4e=16
Simplify: a+b+c+d+e=4
Subtract:
a+b+c+d+e=4
a+b+c+d=1
e=3
To find d with e:
first equation-fifth equation:
a+b+c+d=1
a+b+c=3
d=-2
To find a with d and e:
fifth equation-second equation:
a+b+c=3
b+c=1
a=2
To find b with a, d, and e:
Use fourth equation
-2+3+2+b=4
b=1
To find c with a, b, d, and e
Use fifth equation
3+2+1=6
c=0